Teoretske paradigme sodobne varnosti in okolje kot varnostno vprašanje - Malešič, Marjan (Teorija in praksa, 2012)
The article is based on the assumption that the environmental and security issues of the contemporary world are closely related, and consequently the topic of analysis is the attitude of theoretical security paradigms regarding these issues and their interconnectedness. The hypothesis of the analysis is as follows: to comprehensively understand the relationships between security and the environment one needs to apply the cognitive achievements of all key theoretical security paradigms dealing with the topic, because each of them only sheds light on part of the issue and none of them offers a comprehensive solution to the problem. At the beginning, the article introduces the crucial environmental problems facing contemporary society and their general security implications. It continues with the basic features of each theoretical paradigm to which the analysis of its attitude to the security implications of environmental problems is added. In this part the analysis is, at least to some degree, comparative. In the conclusion, the author tests the ontological and epistemological value of theories that explain the relationship between the environment and security and checks the validity of the hypothesis.
Keywords: natural environment; Okolje; Environment; Safety; security; Varnost; Filozofske teorije; Philosophical theories; realizem; liberalism; liberalizem; konstruktivizem; constructivism; marksizem; Marxism